A representação social do pombo no meio urbano : o simbolismo na praça da bandeira em Campina Grande - Silva, Juliana Tavares da (2006)
This study it presents a contribution for inquiries of the urban aspect of the ambient questions from a psychosocial boarding. Presenting the description-cultural constituent that had originated stereotype of the pigeon and that they influence the imaginary one in the present time, one searched to differentiate them of inherent the biological factors to this bird. Both neither are imaginary part of the popular one and determine behaviors and attitudes in an ecological relation nor always balanced. The relation human being with the natural environment was modified to the long one of the centuries, until propitiating the domination and I overwhelm it of many species. The internal organization of the society also favored the suppliment of the necessities spirituals human beings, and in this way the first birds had been domesticated to revive the life of its owners. The study it was carried through in the Praça da Bandeira, in the city of Campina Grande, Paraíba, Brazil, for this area to present a central and commercial localization in the city, which provides the intense traffic to it of passer-bys, and for also presenting a population of pigeons that remains fixed in the place. The symbolic constituent had been evaluated with theoretical in the Theory of the Social Representations and methodological base in the Theory of the Central Nucleus. One searched to discover the structure and the anchorage of the social representations. The data had been gotten from the free association of ideas, of which had participated 112 people. In the treatment of the data software EVOC was used, and the results had parallel indicated the existence of a representation structuralized around the pigeon idealized to the biological pigeon. It was registered trend to the religious projection on the animal, therefore I appeal it affectiveemotional is intense. The distinction between the emblem and the reality was clear, when the imaginary profile, as part of the symbol, is remained in the virtuous conception while the biological aspects and ambient they come in the daily one, or either, in the direct contact with the animal. The anchorage delineates the relation historical human being with the pigeon under similar parameters to the representational originals. Transformations if they present in an sketch of incorporation of recent sanitary information. This research corroborates the relevance of the Theory of the Social Representations as resource theoretician-metodologic in a perspective of contribution of the knowledge to vernacular inserted in an educative and managing action of the environment